2020
DOI: 10.1021/acsaem.0c00540
|View full text |Cite
|
Sign up to set email alerts
|

γ-ray Radiation on Flexible Perovskite Solar Cells

Abstract: Flexible solar cells are promising for space applications due to their unique properties including lightweight and flexibility. In particular, flexible perovskite solar cells (f-PSCs) with high efficiencies have a much stronger competitiveness, but study about the radiation tolerance of f-PSCs is still absent. Herein, the radiation tolerance of methylammonium (MA)/formamidinium (FA)/cesium (Cs)-based triple cation f-PSCs under γ-ray was investigated systematically, with a planar heterojunction structure of PEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…This low bias voltage (0.1-5 V) offers the possibility of application in energy-sparse environments, for example in space. [37] Furthermore, its maximum photocurrent response of 2.3 µA (Table S1, Supporting Information) reached in less than 500 ms (Figure 2d) is in range with the best values acquired for MHP-based gamma detectors.…”
supporting
confidence: 62%
“…This low bias voltage (0.1-5 V) offers the possibility of application in energy-sparse environments, for example in space. [37] Furthermore, its maximum photocurrent response of 2.3 µA (Table S1, Supporting Information) reached in less than 500 ms (Figure 2d) is in range with the best values acquired for MHP-based gamma detectors.…”
supporting
confidence: 62%
“…The Martian surface environment is a complex system that experiences an extreme climate, the accumulation of dust, and high-energy cosmic radiation, which could lead to interruption of the power output of PSCs. 20,[27][28][29] To simplify the simulation process and focus on investigating the light and temperature effects on the PSC, only light and temperature variations on Mars were simulated without considering other environmental factors in this study. The test environment was set as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for flexible PEN/ITO substrates, the amorphous structure and long carbon chains in polymer may help to eliminate the radiation by altering their orientation and contribute to a better radiation resistance and higher suitability under radiation. After systematically studying the influence of γ-rays with different irradiation doses on the non-encapsulated flexible PSCs, FA 0.945 MA 0.025 Cs 0.03 ­Pb­(I 0.975 Br 0.025 ) 3 -based perovskite films, and PEN/ITO substrates, Huang et al concluded that the attenuation of device performance under γ-ray irradiation was mainly caused by the decrease of substrate transmittance. Smeenk et al also demonstrated that the high-energy UV photons in space environment could induce cleavage of the organic moieties (i.e., C–C or Si–C bonds), leading to decreased polymer chain lengths and discoloration of the transparent polymer substrates.…”
Section: Practical Applications Of Lightweight F-pscsmentioning
confidence: 99%